Three-dimensional polymer coated 45S5-type bioactive glass scaffolds seeded with human mesenchymal stem cells show bone formation in vivo - Westhauser, Fabian; Weis, Christian; Prokscha, Matthäus; Xiao, Kai; Kneser, Ulrich; Kauczor, Hans-Ulrich; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (Journal of materials science, 2016)
45S5-type bioactive glasses are a promising alternative to established substitutes for the treatment of bone defects. Because the three-dimensional (3D) structure of bone substitutes is crucial for bone ingrowth and formation, we evaluated the osteoinductive properties of different polymer coated 3D-45S5 bioactive glass (BG) scaffolds seeded with human mesenchymal stem cells (hMSC) in vivo. BG scaffolds coated with gelatin, cross-linked gelatin, and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) were seeded with hMSC prior to implantation into severe combined immunodeficiency mice. Newly formed bone was evaluated with histomorphometry and micro-computed tomography. Bone formation was detectable in all groups, whereas the gelatin-coated BG scaffolds showed the best results and should be considered in further studies.Graphical Abstract Open image in new window